Aerosolized type II transmembrane serine protease 2 inhibitor to combat COVID-19: a proposal - Raybarman, Chandan; Bhattacharjee, Surajit (International Journal of Contemporary Pediatrics, 2021)
Type II transmembrane serine protease (TMPRSS2) is expressed at the cell surface with COVID-19 infection. And COVID-19 infection misuse TMPRSS2 to advance their spread, making this protease potential focuses for intervention in COVID-19 infection. TMPRSS2 blocker may be the appropriate option to arrest cellular entry of COVID-19 by deregulating spike priming. Therefore a trial may be intended to watch the adequacy of aerosolized spraying of TMPRSS2 inhibitors to break the viral entry to the objective cells that empower to break the COVID-19 transmission. Targeting TMPRSS2 through aerosolized TMPRSS2 inhibitor is important to examine a possibly viable remedial technique in the treatment of COVID-19.